Dairy-Derived and Egg White Proteins in Enhancing Immune System Against COVID-19 - Batiha, Gaber El-Saber; Alqarni, Mohammed; Awad, Dina A. B.; Algammal, Abdelazeem M.; Nyamota, Richard; Wahed, Mir I. I.; Shah, Muhammad Ajmal; Amin, Mohammad N.; Adetuyi, Babatunde O.; Hetta, Helal F.; Cruz-Martins, Natália; Koirala, Niranjan; et al. (Frontiers in Nutrition, 2021)
Coronavirus disease (COVID-19) is a global health challenge, caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) triggers a plethora of respiratory disturbances and even multiple organs failure that can be fatal. Nutritional intervention is one of the key components towards to a proper management of COVID-19 patients, especially in those requiring medication, and should thus be considered the first-line treatment. Immuno-modulation and -stimulation are currently being explored in COVID-19 management and are gaining interest by food and pharmaceutical industries. Various dietary combinations, bioactive components, nutrients and fortified foods have been reported to modulate inflammation during disease progression. Dietary combinations of dairy-derived products and eggs are gaining an increasing attention given the huge immunomodulatory and anti-inflammatory properties attributed to some of their chemical constituents. Eggs are complex dietary components containing many essential nutrients and bioactive compounds as well as a high-quality proteins. Similarly, yogurts can replenish beneficial bacteria and contains macronutrients capable of stimulating immunity by enhancing cell immunity, reducing oxidative stress, neutralizing inflammation and regulating the intestinal barriers and gut microbiome. Thus, this review highlights the impact of nutritional intervention on COVID-19 management, focusing on the immunomodulatory and inflammatory effects of immune-enhancing nutrients.